HR-power relationship during laboratory testing and stage racing in professional male cyclists - Palmer, G. S.; Martin, D. T.; McLean, B. D.; Bannan, S.; Lee, H.; Craig, N. P.; Hawley, J. A. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Heart rate monitors have become a popular tool for evaluating the physiological demands of competition in a variety of sports. The primary aim of this study was to document the heart rate - power output (HR-Watts) relationship established in the laboratory during a graded exercise test (GXT) and during competition. Five Australian Professional male road cyclists (MEAN± SD; 69.9± 6.0 kg, 423± 35 W PPO, 5.21± .44 L.min-1 peak) completed a maximal GXT within two weeks of competing in a six-day stage race. The GXT began at 100 W and increased by 50 W every 5 minutes. During the stage race HR and Watts were recorded every second during stage 1 (ST1RR-104 km), stage 6 (ST6RR-130 km) and stage 7 (ST7CRIT - 40 km) using SRM Power Cranks (Jullich, Germany). During the GXT the HR was measured (Polar, Inc.) at the end of the 5-min stage. During competition, HR and Watts measurements were averaged every minute. A linear regression was performed on the HR-Watts data collected during the GXT and the three races in each of the 5 cyclists. The regression equation was used to calculate HR at 100 W (HR100W) and 300 W (HR300W) for each cyclist. The difference between HR during GXT and races were evaluated using a series of Wilcoxon Matched Pairs Tests. R2 during the GXT was always greater than .96 but ranged from .48-.78 during ST1RR and ST6RR. R2 during ST7CRIT were low, ranging between .02 and .21. HR100W was lower during GXT (97± 6 bpm) than ST1RR (131± 7 bpm, P<.05), ST6RR (118± 5, P<.05) and ST7CRIT (157± 11 bpm, P<.05). In contrast, HR300W during GXT (154± 5 bpm) was similar to ST1RR (159± 4 bpm, NS) and ST6RR (149± 6, bpm, NS) but lower than HR300W during ST7CRIT (166± 6 bpm, P<.05). These data document that 1) the HR-Watts relationship is poor during criterium races, 2) HR at low Watts can be 20-30 bpm higher during a road race than observed in the laboratory, and 3) the laboratory and 1-min average field HR-Watts relationship is similar (within 6 bpm) at higher power outputs (» 300 W) during road races. Differences in temperature, arousal, and the work: relief durations between the laboratory testing and the field conditions could be responsible for unique HR-Watts relationship during competition.